Cutaneous involvement of disseminated adenovirus infection in an allogeneic stem cell transplant recipient. (18th February 2016) - Keyes, A.; Mathias, M.; Boulad, F.; Lee, Y.J.; Marchetti, M.A.; Scaradavou, A.; Spitzer, B.; Papanicolaou, G.A.; Wieczorek, I.; Busam, K.J.
Summary: Infection by human adenoviruses can lead to significant morbidity and mortality in immunocompromised hosts, such as allogeneic stem cell transplant (SCT) recipients, with limited effective treatment options. Specific cutaneous manifestations of disseminated adenovirus infection are not well described. We report a woman in her twenties who received an allogeneic T‐cell‐depleted peripheral blood SCT for the treatment of severe aplastic anaemia and, 5 months post‐transplant, was hospitalized for severe systemic adenovirus infection with progressive involvement of the colon, liver and lungs. Despite therapy with intravenous cidofovir, oral brincidofovir and intravenous immunoglobulin, she had progression of adenoviraemia and dissemination of adenoviral disease. The patient developed a progressive rash characterized by keratotic papules that began on the palms and soles and spread to the entire body. Histopathological examination of skin biopsies of individual skin lesions from the palm and abdomen showed focal acantholytic dyskeratosis and keratinocytes with hyperchromatic nuclei. Several keratinocyte nuclei were immunoreactive for adenovirus. The patient was further treated with ribavirin and adenovirus‐specific cytotoxic T lymphocytes but experienced multisystem progression of adenovirus infection culminating in death. Abstract : What's already known about this topic? Adenovirus infections mainly cause transient respiratory illnesses associated with nonspecific dermatological manifestations, such as morbilliform rash. Cutaneous involvement of disseminated adenovirus infection is not well described. What does this study add? Skin lesions in disseminated adenovirus infections may appear as vesicle‐like, red‐to‐violaceous, keratotic papules that initially favour acral sites. Histopathological features include parakeratotic columns associated with focal acantholytic dyskeratosis and keratinocytes with hyperchromatic nuclei that are immunoreactive for adenovirus.